2019
DOI: 10.1177/1474515119845198
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nurse-led atrial fibrillation clinics on patient and healthcare outcomes: a systematic mixed studies review

Abstract: Background: Atrial fibrillation, the most common arrhythmia worldwide, continues to increase as the population ages. Patients with atrial fibrillation, particularly those newly diagnosed or who have multiple comorbidities, have high healthcare utilisation rates. Nurse-led atrial fibrillation clinics have developed to improve care and guidance for atrial fibrillation patients, with the potential to reduce hospital presentations and healthcare utilisation. Atrial fibrillation clinics that provide specialised and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 38 publications
5
40
0
1
Order By: Relevance
“…36 Regarding usual care. 47,48 The results of our study seem to reinforce the hypotheses of better clinical outcomes in a specific AF clinic led by nurses, since the rate of ischaemic stroke/TIA was significantly lower in the group of patients followed up in this clinic.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…36 Regarding usual care. 47,48 The results of our study seem to reinforce the hypotheses of better clinical outcomes in a specific AF clinic led by nurses, since the rate of ischaemic stroke/TIA was significantly lower in the group of patients followed up in this clinic.…”
Section: Discussionsupporting
confidence: 84%
“…Recent systematic reviews and meta‐analyses shown that, in overall, nurse‐led clinics improved healthcare, patient and quality care outcomes. Mortality rates and cardiovascular hospitalisations are lower, whereas patient medication adherence, quality of life and guideline adherence are higher in nurse‐led AF clinics compared to usual care 47,48 . The results of our study seem to reinforce the hypotheses of better clinical outcomes in a specific AF clinic led by nurses, since the rate of ischaemic stroke/TIA was significantly lower in the group of patients followed up in this clinic.…”
Section: Discussionsupporting
confidence: 76%
“…Of these, results demonstrated that a significant proportion of ED patients are appropriate for safe and effective outpatient management of AF. [15][16][17] These pathways include strategies for early rhythm control, initiation of rate control therapies and anticoagulation for stroke prophylaxis. 15 16 However, due to barriers in implementation, these strategies have yet to be maintained nor fully accepted.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, nurse-led AF clinics were found to be more cost-effective, have shorter wait times and reduce subsequent ED visits and hospitalisations. 17 When compared with standard care, guideline-based medication adherence and patient mortality rates were lower, while quality of life was improved. However, in a study randomising patients with a history of AF to receive nurse-led care or usual care, there was no overall advantage to nurse-led care in a composite of cardiovascular death and cardiovascular hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Speciality nurse-led clinics can reduce waiting times to be seen, get diagnosed and receive hospital-based treatment. These clinics are also associated with reduced rates of hospitalisations and overall healthcare costs (Rush et al, 2019).…”
Section: Guest Editorialmentioning
confidence: 99%